Parent's Responsibility of A Child's Education as Mandated in Quran | الأمانة التربوية على الوالدين نحو الأولاد في ضوء القرآن الكريم - Ahmaddin Ahmad Tohar (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2019)
Education is a mandate burdened for parents. Parents are fully obliged to provide learning to their children so their potential can improve and develop properly. The house is the most ideal school in which can train and progress children's talents and characteristics. also, the most essential is the example from parents to set children to develop with Islamic moral values. an ethical model gives strength to children to trust more themselves in life. An honourable example will produce ahead preferred generations. Parents who do not have moral kindness is impossible to set a good example because people who do not have is impossible to give.